A Qadiriyya Sheikh Mor Ali Baba in Sivas - (:unkn) unknown (CUMHURIYET UNIV, FAC THEOLOGY, 2015)
There are a number of spirituality leaders that become prominent for establishment of the Muslim identity in the Sivas province nearly 1,000 years. Among these leaders the prominent name in reconstruction of the spiritual world in Sivas was Mor (Mur) Ali Baba (1804-1884). Mor Ali Baba moved up from Kirkuk and settled down in Sivas, established Qadiri lodges where he showed the true path, died in Sivas and was buried in the lodge of his own. Ali Baba was a poet and editor in addition to his sufistic identity. He used Ali as nickname in his poets. His date of death was not certain before but it was detected certainly as 1884 with the help of court registries. He had five sons. His older and the second older sons Poet Abdulqadir Qulami (1854-1887) and Seyfeddin served as sheikh in Sivas Qadiri lodge after the death of their father. After the lodges were closed down in 1925, Mor Ali Baba's grandchildren were far away from lodge service. They took the Moral surname and have served as officers.
Keywords: Mor Ali Baba; Sivas; Qadiri; Abdulqadir Qulami; Seyfeddin; Lodge; Ziya Pasha